Development of Local Community-Based Ecotourism in Minahasa Regency - B. Kairupan, Sisca; Mantiri, Jeane; Christy Mowilos, Rebecca (Iapa Proceedings Conference, 2025)
This study aims to analyze the potential, challenges, and formulate a model for the development of community- based ecotourism (CBET) in Minahasa Regency. Minahasa has natural and cultural wealth that has great potential to be used as an ecotourism destination, such as Lake Tondano, Bukit Kasih, as well as traditional cultural and craft sites. However, the utilization of this potential is still not optimal due to various structural challenges such as low human resource (HR) capacity, weak local institutions, inadequate infrastructure, and lack of community participation. Through a qualitative approach with data collection techniques in the form of in-depth interviews, field observations, and document studies, this study reveals that the success of ecotourism development in Minahasa is highly dependent on the integration of three pillars of sustainability: social, economic, and environmental. The results of the study recommend the need for regional policy interventions that support inclusive governance, strengthening local institutions, and supervision strict environment. With a participatory and adaptive approach to local conditions, the CBET model is considered to be able to make ecotourism an instrument of environmental conservation as well as a driver of the people’s economy in Minahasa Regency.